Assessing the Impact of Requiring Justification and Approval Review for Sole Source 8(a) Native American Contracts in Excess of $20 Million - Moore, Nancy Y. (RAND Corporation, 2012)
Participants in the federal 8(a) Business Development Program can receive low-value procurement contracts without competitive bidding; certain firms can receive contracts of any size. Concern over these firms' advantage led Congress to require a justification and approval process for contracts over $20 million. The effect is still emerging, but it may delay large contracts more than reduce the number awarded because the underlying need remains.